Perceptions of students in colleges belonging to the science and technology cluster of the University of the Philippines Diliman on Library and Information Science - Santos, Jonathan F.; Buenrostro, Iyra S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study was undertaken to determine how non-Library and Information Science (LIS) students of the University of the Philippines Diliman, particularly students belonging to the Science and Technology Cluster courses, perceive the field of LIS and the factors that affect their perceptions.
This study used the descriptive method of research with survey questionnaires as primary instruments to gather the essential data. From a population of 6,220 undergraduate students belonging to the colleges of Engineering, Home Economics and Science, 376 were selected as samples of the study by using quota (non-probability) sampling.
Based on the gathered data, the following conclusions were made: (a) non-LIS students nowadays somehow have insight on what the field of LIS is all about despite the lack of sources of information about the field; (b) the claim that "the status of the library and information profession is low" is not widely accepted anymore; (c) people somehow believe in the importance of having libraries and vital role that LIS professionals play in our society but because of the lack of information on LIS, people are left undecided whether the image and status of LIS is good or not; (d) poor stereotyping, low salary, insufficient information, and clerical work still affect the way people perceive the image and status of LIS negatively, however, computerization and use of technology in library services affect positively; and (e) the field of LIS is not that popular among undergraduate students in the University of the Philippines Diliman, being ranked 14th among 15 professional fields by students belonging to the three colleges.
Recommendations to improve the image and status of LIS include: (1) for libraries and information centers to focus more on improving their services through the use of technology; (2) for LIS schools and organizations in the country to become more active in promoting awareness among the public as well as students about what LIS is about; (3) for future LIS researchers and professional in UP Diliman to conduct studies about the effectiveness of having a General Education course about LIS and the possibilities of having its own building; (4) for librarians, library staff and other library personnel to observe good attitude and to give the students and other users the proper treatment that they deserve; and (5) for LIS professionals to continuously make improvements on the equipment and facilities that are being used in the field and create new ideas that will make the students and users appreciate the field.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines (Diliman) -- Students; Library science; Information science